Pain and Suffering in Cancer Patients. Issue 2 (1st January 2015) - Munglani, Rajesh; Bhaskar, Arun
Abstract: Pain affects most cancer patients due to the disease itself or its treatment and recent studies indicate that persistent severe pain continues to be prevalent despite advances in treatment. The World Health Organization (WHO) ladder and liberal use of opioids still do not provide adequate pain relief in a quarter of patients and pain medicine consultants are often able to help many of them. Unfortunately despite all possible interventions we recognise that a small number of patients still continue to suffer severe uncontrolled pain. In others, whilst the severe physical pain may be controlled, they continue to suffer 'mental and emotional pain' in the form of suffering and loss of autonomy and may undergo existential crises. As such, questions as to the role of medicine, whether to relieve suffering in all its forms or simply to maintain existence without due regard for quality of life are raised.